Tribological performance of palm oil-based lubricant with nanoparticles additive / Mohamad Faizal Rosli - Mohamad Faizal , Rosli (2019)
Lubrication is an essential tool in human life. As the technology advances, the method of lubrication becoming a lot complex and we relied heavily on mineral oil or synthetic oil which are harmful for the environment. Researchers around the world have started to shift their focus on bio-lubrication that is more environmentally friendly. Bio-lubricant based on palm oil could be one of the best replacements of standard lubricant. With nanoparticle additives, the tribological performance of the bio-based lubricant could be improved even more. This investigation will be centred around the tribological characteristic of bio based trimethylolpropane (TMP) ester with nanoparticle and nanocomposite additive. Additives that in focus are Copper Oxide (CuO) and Titanium Dioxide (TiO2). The nanocomposites are the mix of both nanoparticles with different configuration ratio. The aim of the investigation is to obtain the tribological performance of all the targeted samples and compare it to understand the best sample in term of tribology. It is found that the bio based TMP ester have tribological potential against the conventional PAO8. For nanoparticles, Copper Oxide shown that the concentration of 0.1 wt.% produced the best tribological performance against other tested concentration. Titanium Dioxide nanoparticle with concentration of 0.1 wt.% also produced the best tribological performance against other tested concentration. For nanocomposite, it found that the configuration ratio of 1 Copper Oxide to 2 Titanium Dioxide yields the best tribological performance against other tested configuration ratios.